PENGARUH WORK FAMILY CONFLICT DAN STRES KERJA TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Nandytama, Wiryawan Syah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Employees at the company PT. xyz experienced indications of conflict and work stress affecting Turnover Intention. PT. xyz is a company that works in the service sector, namely expeditions and coal sales in South Kalimantan. The company's legal entity status at this time is a limited liability company. PT xyz has been serving the domestic market throughout Indonesia. The company currently has offices in 2 locations, namely in South Kalimantan and in the city of Gresik. The object of this research was carried out at the PT xyz branch office located in the city of Gresik. The aim of this research is to test and analyze the influence of work family conflict and work stress on turnover intention with job satisfaction as a moderating variable in PT xyz employees. This investigation uses a field investigation approach to collect data at the investigation location. This method is categorized as a quantitative investigation methodology, which focuses on collecting and analyzing numerical data to produce objective and measurable conclusions. 56 respondents were employees from the Office of PT xyz. This study uses a purposive sampling technique to take based on certain considerations.The results of this study explain that work family conflict has a positive and significant influence on turnover intention, work stress has a positive and significant influence on turnover intention, job satisfaction does not moderate the relationship between work family conflict and turnover intention, job satisfaction does not moderate the relationship between work stress on turnover intention